Neurosensory alterations and function of the temporomandibular joint after high oblique sagittal split osteotomy: an alternative technique in orthognathic surgery - Seeberger, Robin; Asi, Yamen; Thiele, Oliver C.; Hoffmann, Jürgen; Stucke, Kathrin; Engel, Michael (The British journal of oral & maxillofacial surgery, 2013)
The current most common technique for repositioning of the mandible, bilateral sagittal split osteotomy (BSSO), was first described by Obwegeser and Dal Pont in the early1960s, and has since been modified several times. However, there is always a risk of damaging the inferior alveolar nerve. We have studied 50 consecutive patients who had high oblique sagittal split osteotomy (HSSO) as an alternative to avoid damage to the nerve. The patients were evaluated for sensory alterations and function of the temporomandibular joint (TMJ). Healing of both wound and bone were complete and uneventful in all 50 patients. Mean (SD) sagittal movement of the mandible was 6.6 (2.9)mm and length of the osteotomy line was 11.0 (3.1)mm. No patient had either temporary or permanent alteration in sensitivity. Pinprick tests showed no significant changes between the preoperative and postoperative readings (p>0.16) or in the chronological results (p>0.23). No disorders of the TMJ developed. Mean (SD) mouth opening 6months postoperatively was 41.6 (8.6)mm. The lateral excursion increased postoperatively by 1.86mm to the left and by 0.76mm to the right. Protrusion increased by 0.66mm. HSSO is therefore a suitable alternative to BSSO as it avoids injury to the inferior alveolar nerve without compromising the TMJ. Ossification was uneventful though bony attachment was less than with the classic BSSO.
Available online 20 December 2012
Gesehen am 26.06.2018